Impact of reversionary and other etiological factors on prognosis and course of schizophrenia - Ifeta Ličanin; Amira Redžić (Medicinski Glasnik, 2010)
Aim To identify the presence of schizophrenia among patients andtheir relatives, factors affecting duration and prognosis of the disease and other etiological factors related to schizophrenia.Methods This retrospective, descriptive, analytical and epidemiological research, which was conducted at the Psychiatric hospital of the Clinical Center of the University of Sarajevo during 2007, covered randomly selected 100 hospitalized patients with schizophrenia according to diagnostic criteria of the Diagnostic andStatistical Manual of Mental Disorders (DSM-IV). Diagnosis of schizophrenia among relatives was based on anamnesis- Structural Clinical Interview (SCID) and it was applied to confirm DSM-IV diagnosis of schizophrenia. Results The presence of schizophrenia among patient relatives was the most important in etiology of schizophrenia (62%), and etiological factors were represented in 38 % of examinees (p=0,0001). Among relatives of examinees aged 20 – 30 years, schizophrenia was present in 37 (59.7%) cases. Schizophrenia among relatives caused earlier appearance of the disease. Duration of hospitalization of over 60 days was in the group of examinees which have the relatives with schizophrenia, 18 (29.0%); multiple hospitalizations were noted in the group of relatives in 40 (64.5%) cases; in one case (8.3%) traumatic experience was noted, in three (42.8%) acute stress, and in four 4 cases (28.6%) non-adequate living conditions. Conclusions The results of this study show that reversionary factors are responsible for inducing schizophrenia, which leads towards chronic course of the disease and worsened prognosis.